Guizhi Fuling Wan, Chinese Herbal Medicine, Ameliorates Insulin Sensitivity in PCOS Model Rats With Insulin Resistance via Remodeling Intestinal Homeostasis - Zhu, Ying; Li, Yin; Liu, Min; Hu, XiaoDan; Zhu, Hongqiu (Frontiers in Endocrinology, 2020)
Polycystic ovary syndrome (PCOS) is a common endocrine disease with reproductive dysfunction and metabolic disorder in women of childbearing age. Gastrointestinal microbiome contributes to PCOS through mediating insulin resistance. Cassia twig tuckahoe pill, Chinese herbal medicine, can treat PCOS with insulin resistance (IR), but the underlying mechanism is not clear. Here, we try to investigate whether the mechanism of action of cassia twig tuckahoe pill is related to regulate the intestinal flora structure. 60 six-week old female SD rats were randomly divided into blank control group, model control group, Cassia twig tuckahoe pill low, middle and high dose group and positive drug(metformin) control group. Fasting blood glucose and fasting insulin in each group were determined by Radioimmunoassay, the data display that the level of fasting blood glucose, fasting insulin in Cassia twig tuckahoe pill low, middle and high dose group and positive drug control group is significantly decreased compared with model control group. Gut microbiota between blank control group and model control group was significantly different, determined by 16S rDNA amplicon sequencing. Compared with the blank control group, the relative abundance of Firmicutes and Proteobacteria increased, while Bacteroidetes, Alloprevotella and Bifidobacterium decreased. Compared with the model control group, Cassia twig tuckahoe pill high dose group can significantly increase the relative abundance of Firmicutes, reduce the relative abundance of Proteobacteria, Bacteroidetes and Enterobacteiales. These results indicate cassia twig tuckahoe pill can improve insulin resistance in polycystic ovary syndrome and the underlying mechanism is to influence intestinal microecological structure and remodeling intestinal homeostasis.